Análisis a los Estados Financieros del ̈Sindicato de Choferes Profesionales de Zamora Chinchipe ̈ de la ciudad de Zamora Periodos 2020-2021. - Armijos Rosales, Jhonatan Andres (2023)
The Curricular Integration Project titled: Analysis of the financial statements of the “Professional Drivers Union of Zamora Chinchipe” in the Zamora city for the Periods 2020-2021, was conducted with the objective of comprehending the current financial standing of the union. This research work implemented strategic measures that facilitated the attainment of the established objectives and goals. The development of the project began with gathering information through an interview conducted with the Accountant, enabling a deeper understanding of the entity's current state. Therefore, this study is focused on the analysis and interpretation of the economic and financial situation, with the objective of making well- informed decisions. The present research work has the following specific objectives: to develop a vertical analysis of the financial statements, detailing the financial structure and the proportional percentages of each account influencing the economic and financial position of the union. Additionally, a horizontal analysis of the financial statements was conducted, delineating financial movements and variations, including increases and decreases in figures within the financial statements during the study periods. Similarly, financial indicators of liquidity, activity, solvency, and profitability were applied, enabling the determination of liquidity for the last period, a value enabling the response to short-term obligations. Finally, a concise financial report was prepared, presenting the results of the conducted analysis. After this, corresponding conclusions and recommendations were formulated, intended for the purpose of guiding the decisions to be made by the Drivers' Union.